LEVELS OF TOTAL PETROLEUM HYDROCARBONS (TPH) AND HEAVY METALS IN SHRIMP WASTE MEAL SUPPLEMENTED BROILER FEEDS AND DROPPINGS (Biological Sciences - PJSIR, 2004)
The study determined the levels of cadmium, lead and total petroleum hydrocarbons (TPH) in shrimp waste meal supplemented feeds and droppings of the broiler birds. The samples were collected randomly over a period of two months. Cadmium and lead were determined by atomic absorption spectrophotometry, while total petroleum hydrocarbons (TPH) were determined gravimetrically by following standard methods. The results show for cadmium 0.61 ± 0.48 mg / g and 0.81 ± 0.32 mg / g, respectively; 9.49 ± 2.24 mg / g and 11.49 ± 1.55 mg / g for lead; 369.00 ± 108.40mg / g and 330.20 ± 59.03 mg / g for TPH, respectively for the starter and finisher feeds. The statistical analysis of vari-ance reveal significant differences at 95% confidence level for lead and TPH compared with control samples. The droppings of the broilers were also collected and analysed with statistically significant difference existing for lead.